2006
DOI: 10.1038/sj.onc.1209419
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of iNOS by the p44/42 mitogen-activated protein kinase pathway in human melanoma

Abstract: Activating mutations of the genes for NRAS and BRAF, components of the p44/42 mitogen-activated protein kinase (MAPK) pathway, are common findings in melanoma. Recent evidence in several nonmelanoma cell systems supports the regulation of the inducible nitric oxide synthase (iNOS) gene by this pathway. On the basis of our data showing that melanoma iNOS expression predicts shortened patient survival, we formulated the hypothesis that activating mutations of NRAS or BRAF, which lead to constitutive activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 28 publications
0
23
2
Order By: Relevance
“…Lim et al showed that the PI3K-Akt pathway phosphorylates and activates eNOS, resulting in the activity of H-Ras and NRas and tumor growth (36). In addition, other previous studies reported NO-induced cell proliferation and cell invasion (38,39). The authors of these reports argue that NO-induced activation of Erk-1/2 leads to cell survival, in opposition to our data indicating the tumoricidal effects of NO.…”
Section: Discussioncontrasting
confidence: 56%
“…Lim et al showed that the PI3K-Akt pathway phosphorylates and activates eNOS, resulting in the activity of H-Ras and NRas and tumor growth (36). In addition, other previous studies reported NO-induced cell proliferation and cell invasion (38,39). The authors of these reports argue that NO-induced activation of Erk-1/2 leads to cell survival, in opposition to our data indicating the tumoricidal effects of NO.…”
Section: Discussioncontrasting
confidence: 56%
“…Our results show increased Akt phosphorylation at Ser 473 in the hearts of obese female rats, which further support the hypothesis that Akt regulates NFκB activity and thereby iNOS expression. Moreover, the role of ERK1/2 in iNOS activation has been demonstrated and increased ERK1/2 phosphorylation usually upregulates both NFκB activity and iNOS protein expression [46,49,[61][62][63]. However, in the present study there were no differences in ERK1/2 phosphorylation between obese and control female rats.…”
Section: Interestingly Mariappan Et Al Reported Increased Nfκb Exprcontrasting
confidence: 54%
“…Cells in OptiMEM media were transfected with 200 nmol/L Mcl-1 -specific or Bcl-2 -specific siRNA or Negative Control siRNA using Oligofectamine reagent (Invitrogen) according to manufacturer's transfection protocols and to ref. (85). After 5 h, 1 mL of growth media was added to the transfection media, and 24 h later, the media was completely replaced by growth media.…”
Section: Rna Interferencementioning
confidence: 99%